O direito à sadia qualidade de vida e a síndrome de burnout enquadrada como doença ocupacional no Brasil - Guimarães, Abraão Lucas Ferreira (2024)
This study investigates burnout syndrome in Brazil and its classification as an occupational disease, exploring its causes, symptoms and consequences. Using a qualitative approach based on semi-structured analyses, organizational factors were identified, such as excessive workload and lack of institutional support, as well as individual factors, such as lack of skills to deal with stress, as the main triggers of burnout. The results revealed a significant prevalence of the syndrome among participants, with symptoms ranging from emotional exhaustion to depersonalization and low personal fulfillment. Furthermore, negative consequences were identified for the quality of patient care and the well-being of professionals. This study highlights the importance of multifaceted interventions, including organizational support, self-care programs and development of stress management skills, to mitigate the impact of burnout and promote mental health and quality of care, in which Brazilian legislation plays a crucial role. in preventing and caring for burnout, establishing limits on working hours and working hours, providing occupational health programs and promoting awareness on the topic.